STUDI JENIS DAN PEMANFAATAN BAMBU OLEH MASYARAKAT DUSUN PERIGI DESA SEMADE KECAMATAN BANYUKE HULU KABUPATEN LANDAK - Jong, Yeriko; Wardenaar, Evy; Tavita, Gusti Eva (Universitas Tanjungpura, 2018)
Bamboo is one of the non-timber forest products (NTFP’s) used by the community to make handicrafts. Therefore, providing information to find out the variety and the utilization of bamboo is needed. This study aims to determine the variety and parts of bamboo that can be utilized. The study was conducted for 1 month, starting from June 26, 2017 to July 24, 2017. It was conducted in community-owned forest area of Perigi sub-village Semade village Banyuke Hulu sub-district Landak disctrict. The research was conducted by using descriptive method on community. Sampling was taken by using purposive sampling, specifically respondents who have wide knowledge towards local name of the bamboo, the benefits or the usefulness of bamboo and the high intensity of bamboo utilization. The total number of respondents are 20. The result of identification are 5 bamboo species namely Bambu Aur (Bambusa blumeana), Bamboo Betung (Dendrocalamus asper), Bamboo Buluh (Schizostachyum brachycladum), Bamboo Munti (Gigantochloa hasskarliana), Tamiang (Schizostachyum blumei Ness). The stages in bamboo utilzation process are: logging process, cutting process, cleaning process, drying process, weaving process. The products made by the community are: bakul, capin, nyiru, takin, and raga.Keywords: bamboo, community, Study of variety, utilization.